Salidroside ameliorated hypoxia‐induced tumorigenesis of BxPC‐3 cells via downregulating hypoxia‐inducible factor (HIF)‐1α and LOXL2. Issue 1 (4th June 2019) - Chen, Xiaoping; Kou, Yubin; Lu, Yunsong; Pu, Yumei
Abstract: Herein, we found that salidroside suppressed hypoxia‐inducible factor 1 alpha (HIF‐1α) and lysyl oxidase‐like protein 2 (LOXL2) within human pancreatic cancer BxPC‐3 cells cultured both under normoxia and hypoxia condition. To investigate the effect of salidroside on tumorigenesis of BxPC‐3 cells and whether HIF‐1α and LXCL2 were involved in this process, cells transfected with or without LOXL2 overexpression vector, were treated with 50 μg/mL of salidroside or 50 μM of KC7F2 (a HIF‐1α inhibitor) under hypoxia. Cell viability and invasion were assessed using CCK‐8 and Transwell chamber assay, respectively. Expression of E‐cadherin and matrix metalloproteinase 2/9 (MMP 2/9) was determined, by Western blot analysis, to assess cell mobility at molecular levels. We confirmed that hypoxia increased LOXL2 and induced tumorigenesis of BxPC‐3 cells, as evidenced by promoted cell proliferation and invasion, enhanced MMP2/9 while reduced E‐cadherin. Interestingly, hypoxia‐induced carcinogenesis was significantly retarded by both salidroside and KC7F2, however, enhanced with LOXL2 overexpression. Besides, salidroside and KC7F2 reduced LOXL2, and reversed the tumorigenesis of BxPC‐3 cells induced by LOXL2 overexpression. Given the inhibitory effect of salidroside on HIF‐1α expression, our data suggested that: (1) LOXL2 was the mechanism, whereby salidroside and KC7F2 showed inhibitory effect on cancer progression of BxPC‐3 cells; (2) salidroside exerted its anticancer effect, most likely, by a HIF‐1α/LOXL2 pathway. In conclusion, salidroside was a novel therapeutic drug in pancreatic cancer, and downregulation of HIF‐1α and LXCL2 was the underlying mechanism.